Cytotoxic Activity of Pentacyclic Triterpene-3-Heptadecanoate Ester against Hela Cell Line and Its Docking Study - Sri Mulyani Mulyadi; Tri Yuliati; Maulana Tegar; Imam Ardhila (MPI (Media Pharmaceutica Indonesiana), 2016)
Pentacyclic triterpene-3-heptadecanoate (12,13-dihydro-α-amyrin-20,30-en-3-heptadecanoate)ester refers to the compound as a result of reaction between pentacyclic triterpene-3-ol(12,13-dihydro-α-amyrin-20,30-en-3-ol) and heptadecanoic acid. This research was aimed to conductcytotoxicity test of pentacyclic triterpene-3-heptadecanoate; 12,13-dihydro-α-amyrin-20,30-en-3-oland 12,13-dihydro-α-amyrin-20,30-en-3-acetate esters against Hela cell line. The activity assay wascarried out using MTT method. The results indicated that IC50 value of 12,13-dihydro-α-amyrin-3-heptadecanoate; 12,13-dihydro-α-amyrin-20,30-en-3-acetate and 12,13-dihydro-α-amyrin-20,30-en-3-ol were 111.0, 151.1 and 944.4 μg/ml, respectively. The compound of 12,13-dihydro-α-amyrin-20,30-en-3-heptadecanoate had the lowest IC50 value, suggesting it has a potency to be synthesized as ananticancer drug.